Regulasi Islamic Distribution of Properties Melalui Mekanisme Non Ekonomi di Indonesia - Chandra Maharani; Marnita, Marnita; Baiti Ningsih; Indah Savira (LPPM Universitas Ekasakti Padang, 2024)
This research aims to first, Model the Islamic Distribution of Properties Through Non-Economic Mechanisms in Indonesia. Second, Islamic Distribution of Properties Through Regulation of Non-Economic Mechanisms in Indonesia. Third, Implementation of Islamic Distribution of Properties Through Non-Economic Mechanisms in Indonesia. The research method used is a Normative Juridical approach, which is a type of qualitative research, with a Statute Approach, using descriptive-analytical methods, applying data collection techniques through literature and library studies, interviews accompanied by observations of applications occurring in the community. A fundamental transformation is needed in the Islamic Distribution of Properties through Non-Economic Mechanisms in the form of regulations on Zakat, Waqf, Inheritance, Grants, and Wills in Indonesia to bridge the wide gap between the potential and realization of Islamic Social Funds (DSI). This research aims to formulate such a transformation.